PENGARUH PARTISIPASI DALAM ANGGARAN DAN KEJELASAN SASARAN ANGGARAN SERTA PERAN MANAJERIAL PENGELOLAAN KEUANGAN DAERAH TERHADAP KINERJA PEMERINTAH DAERAH (Studi Empiris pada Pemerintah Provinsi Bengkulu) - Nur Emilia, Rahmi; Abdillah, Willy; Abdullah, Abdullah (UNIB Press, 2013)
In order to achieve good governance, the government continues to make efforts to improve the administrative system as a whole and applying state budget goal clarity accordance with the purposes of the budget and to realize that a good managerial role. Thus, the influence of participation in budgeting and budget goal clarity and managerial leadership roles working unit is concerned in improving government performance. This research is quantitative research, which will examine the effect of budgetary participation and budget goal clarity and managerial roles of financial managers on the performance of the local government area of the province of Bengkulu. The population in this study were all SKPD in Bengkulu province consisting of 43 on education, in which questionnaire distributed in each of the 3 leaders representing every subdivision, in order to obtain 129 samples. Based on this research, it was found that, participation in the budget significantly affect the performance of the government with a significant value of less than 0.05, ie 0.000. Similarly, the budget goal clarity variables have a significant influence on the performance of the government with significant value of 0.007, while the role of managerial variables do not significantly affect the performance of the government, with a value significantly greater than 0.05, which is 0.624. Simultaneously, participation in the budget, the budget goal clarity and managerial roles have a significant influence on the performance of the government.